2002
DOI: 10.1046/j.1526-4610.2002.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Magnesium Load Test in Patients With Migraine

Abstract: Magnesium retention occurs in patients with migraine after oral loading, suggesting a systemic magnesium deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…A lowered magnesium level in cellular concentrations could be an indicator of low cerebral levels, which could add to a lowered threshold for migraine headaches. A magnesium load test study (Trauninger et al 2002) revealed that greater retention of magnesium occurred in patients suffering from migraines compared to healthy controls, suggesting a systemic deficiency. A 2-week trial revealed that when migraine patients drank water with magnesium, their total magnesium significantly increased in erythrocytes.…”
Section: Pathophysiologymentioning
confidence: 99%
“…A lowered magnesium level in cellular concentrations could be an indicator of low cerebral levels, which could add to a lowered threshold for migraine headaches. A magnesium load test study (Trauninger et al 2002) revealed that greater retention of magnesium occurred in patients suffering from migraines compared to healthy controls, suggesting a systemic deficiency. A 2-week trial revealed that when migraine patients drank water with magnesium, their total magnesium significantly increased in erythrocytes.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, subjects in the Mg 2+ group showed slight rises in urinary Mg 2+ (+9 to 11%) while those in placebo group showed a substantial decrease in urinary Mg 2+ (-32%). Possibly the decreased urinary Mg 2+ excretion in the placebo cream group represents more active physiological Mg 2+ retention processes that are not apparent in the Mg cream group ([15,16]. It has been suggested that 24-hour urine excretion of Mg 2+ may be a better indicator of tissue status than the serum Mg 2+ concentration, but it is highly variable and it is questionable whether it can be used to reliably assess a given individual’s Mg 2+ status.…”
Section: Discussionmentioning
confidence: 99%
“…Since less than 1% of magnesium is contained in the blood, assessment by serum status may be problematic [3]. It is often considered that 24-hr urine excretion of Mg 2+ may be a better indicator of intestinal absorption than serum concentration; however, urinary Mg 2+ excretion is also highly variable and it is questionable whether it can be used reliably to assess an individual’s Mg 2+ status [15]. However, serum Mg 2+ can reflect a longer term dietary Mg 2+ status over weeks or months whilst urinary Mg 2+ can be a better marker of one’s recent dietary intake [16].…”
Section: Introductionmentioning
confidence: 99%
“…62 Studies have shown that migraineurs have low brain magnesium during migraine attacks 63 and may also have a systemic magnesium deficiency. 64,65 Furthermore, a deficiency of magnesium may play a particularly important role in menstrual migraine. 66 Two double-blind, placebocontrolled trials have shown that oral magnesium supplementation is effective in headache prevention.…”
Section: Vitamins and Other Supplements In The Prevention Of Migrainementioning
confidence: 99%